Order Picking Using Augmented Reality - Martin Krajcovic; Gabriela Gabajova; Branislav Micieta (Communications - Scientific letters of the University of Zilina, 2014)
This article examines the problem of application of augmented reality in terms of picking goods in static systems with the deployment of a man (systems „goods to man“). Article describes a comprehensive methodology for the use of augmented reality in the process of picking starting from the preparation of input data, through optimizing the movement of workers in the warehouse, to actual worker navigation using augmented reality. The problem was solved on the authors´ workplace and the proposed solution has been verified in the experimental workplace built under the concept of ZIMS (Zilina Intelligent Manufacturing System) which is developed at the University of Zilina in cooperation with the Central European Institute of Technology (CEIT).